2010
DOI: 10.1080/09540121003615137
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with risk for unprotected receptive and insertive anal intercourse in men aged 40 and older who have sex with men

Abstract: The frequency of HIV infection is increasing in men who have sex with men (MSM) aged 40 and older yet little is known about factors that influence their risky sexual behavior, such as sexual positioning. The goal of this study was to examine multi-level factors associated with unprotected receptive anal intercourse (URAI) and unprotected insertive anal intercourse (UIAI) in MSM aged 40 and older. A community-based sample of 802 self-identified MSM aged 40-94 years was recruited through targeted outreach from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 31 publications
3
48
2
Order By: Relevance
“…Finally, despite three decades of extant research on sexual behaviors associated with the acquisition of HIV and other sexually transmitted infections (STIs) among gay men (Halkitis, 2010), there is limited knowledge regarding the general sexual health of older gay men in the United States (e.g., Jacobs, Fernandez, Ownby, Bowen, Hardigan, & Kane, 2010), and what is known is often related to the sexual health of those who are seropositive . While the bulk of this research has focused on understanding risk behaviors associated with HIV/STI acquisition and transmission, sexual health encompasses partnership, activity, behavior, attitudes, and function that may be more relevant to the lives of aging gay men.…”
Section: Health States Of Aging Gay Menmentioning
confidence: 98%
“…Finally, despite three decades of extant research on sexual behaviors associated with the acquisition of HIV and other sexually transmitted infections (STIs) among gay men (Halkitis, 2010), there is limited knowledge regarding the general sexual health of older gay men in the United States (e.g., Jacobs, Fernandez, Ownby, Bowen, Hardigan, & Kane, 2010), and what is known is often related to the sexual health of those who are seropositive . While the bulk of this research has focused on understanding risk behaviors associated with HIV/STI acquisition and transmission, sexual health encompasses partnership, activity, behavior, attitudes, and function that may be more relevant to the lives of aging gay men.…”
Section: Health States Of Aging Gay Menmentioning
confidence: 98%
“…Validated psychosocial scales were also included in the questionnaire but are not included in this analysis as they were not required for the focus of this study. Information on the scales used in this study can be found in our previous publications (Jacobs et al, 2010;Jacobs & Kane, 2012).…”
Section: Instrumentmentioning
confidence: 99%
“…Previous studies (Darrow et al, 2005;Lyons, Chandra, Goldstein, & Ostrow, 2010;Ostrow et al, 2009;Semple, Strathdee, Zians, & Patterson, 2010;Wells, Golub, & Parsons, 2011) have linked drug use in MSM men to risky sexual behaviors and to higher rates of HIV infection, but most of these studies have focused primarily on specific time points and on younger MSM. A few studies have written about or investigated drug use as risk for HIV in older MSM populations (Heath, Lanoye, & Maisto, 2011;Jacobs et al, 2010;Ostrow et al, 2009), but they were not specific to HIV-negative older MSM. More data are needed to understand how drug use affects risky sexual behaviours among MSM with negative serostatus in mid-and later life.…”
Section: Unprotected Receptive Anal Intercoursementioning
confidence: 99%
See 2 more Smart Citations